Phonetic-Phonological Analysis of the Formation of Hypochoristics in Singa (Huamalíes-Huánuco) - Mere Collazos, Milagros Jessica (2018)
This research focuses on a description of the phonetic-phonological processes that are involved in the formation of hypocoristics in Singa district, place where there is contact between Quechua and Spanish. The study is based on the theoretical basis of onomastics, linguistic affectivity and language contact. From the analysis, it was determined that one of the most frequent procedures and that evidence Quechua influence is the vowel rise of /e/ and /o/, as well as palatalization.